Studies toward the synthesis of potent anti-inflammatory peptides solomonamides A and B: synthesis of a macrocyclic skeleton and key fragment 4-amino-6-(2 `-amino-4 `-hydroxyphenyl)-3-hydroxy-2-methyl-6-oxohexanoic acid (AHMOA) - Kashinath, K.; Vasudevan, N.; Reddy, D. Srinivasa (Organic Letters, 2012)
A first synthetic effort toward total synthesis of highly potent solomonamides is disclosed. An efficient strategy to synthesize this class of compounds, along with the synthesis of a core macrocycle (shown in red) and the key fragment AHMOA, is described.

Total synthesis of deoxy-solomonamide B by mimicking biogenesis - Vasudevan, N.; Kashinath, K.; Reddy, D. Srinivasa (Organic Letters, 2014)
A total synthesis of Deoxy-solomonamide B was accomplished starting from tryptophan in an efficient manner by mimicking the proposed biogenetic route. The present synthesis utilizes a crotylation, oxidative cleavage of the indole moiety, and macrolactamization as key steps. The use of the indole nucleus as a masked anthranilic acid unit paves the way for the easy synthesis of related macrocycles and natural products where the ortho-acyl aniline moiety is embedded into them, which otherwise is difficult to synthesize.

Breaking and making of rings: a method for the preparation of 4-quinolone-3-carboxylic acid amides and the expensive drug ivacaftor - Vasudevan, N.; Jachak, Gorakhnath R.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2015)
A simple and convenient method to access 4-quinolone-3-carboxylic acid amides from indole-3-acetic acid amides through one-pot oxidative cleavage of the indole ring followed by condensation (Witkop-Winterfeldt type oxidation) was explored. The scope of the method was confirmed with more than 20 examples and was successfully applied to the synthesis of the drug Ivacaftor, the most expensive drug on the market.
Keywords: Amides; Drug design; Fused-ring systems; Oxidation; Ozonolysis

Repurposing Ivacaftor for treatment of staphylococcus aureus infections - Thakare, R.; Das, S.; Vasudevan, N.; Jachak, G.R.; Reddy, D.S.; Dasgupta, A.; Chopra, S. (International Journal of Antimicrobial Agents, 2017)
Drug repurposing of non-antimicrobials is a novel method to augment a seriously depleted drug pipeline for targeting drug–resistant pathogens. This article highlights the potent antimicrobial activity of Ivacaftor against Staphylococcus aureus, including vancomycin– and other multidrug–resistant strains. The potent activity of Ivacaftor in vivo is also demonstrated in a murine neutropenic thigh infection model. Taken together, these results support the potential of Ivacaftor as an antimicrobial agent for the treatment of staphylococcal infections. © 2017 Elsevier B.V. and International Society of Chemotherapy

Multi-step continuous flow synthesis of the cystic fibrosis medicine ivacaftor - Vasudevan, N.; Sharma, Mrityunjay K.; Reddy, D. Srinivasa; Kulkarni, Amol A. (Reaction Chemistry & Engineering, 2018)
A continuous flow ozonolysis method combined with a multi-step flow sequence is developed for the synthesis of the drug ivacaftor for the first time. Safe ozonolysis, a continuous flow quadruple reaction to construct a quinolone scaffold, and inline extraction followed by continuous phase separation are the key features of the present work. The feasibility of using a continuous mixed flow reactor, commonly referred to as a continuous stirred tank reactor (CSTR), is also investigated for the relatively slow reaction step. The current integrated multi-step flow synthesis can produce 7.2 g of the drug ivacaftor per day on a laboratory scale, which is sufficient to treat 50 patients per day. The present route can also be used as a general route for the synthesis of other related drugs such as quinolone antibiotics.

Synthesis of alpha-ketoamides using potassium superoxide (KO2) as an oxidizing agent - Vasudevan, N.; Routholla, Ganesh; Illa, Giri Teja; Reddy, D. Srinivasa (Tetrahedron, 2020)
A simple and convenient method for the synthesis of alpha-ketoamides by the oxidation of aryl acetamides using potassium superoxide (KO2) as an oxidizing agent is disclosed here. The scope of the developed method is successfully tested with fifteen substrates. In addition, the utility of method has been demonstrated by synthesizing an orexin receptor antagonist, a medicinally interesting compound. (C) 2020 Published by Elsevier Ltd.
Keywords: alpha-Ketoamide; Orexin receptor; Oxidation; Potassium superoxide (KO2)

Comprehensive study on solomonamides: total synthesis, stereochemical revision, and SAR studies toward identification of simplified lead - Jachak, Gorakhnath R.; Kashinath, K.; Vasudevan, N.; Athawale, Paresh R.; Choudhury, Rahul; Dange, Santoshkumar S.; Agarwal, Heena; Barthwal, Manoj Kumar; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2023)
Solomonamides, a pair of macrocyclic peptide natural products originating from marine sources, have garnered significant attention within the synthetic community owing to their marked anti-inflammatory efficacy and intricate molecular architectures. In this paper, we present a very detailed investigation into solomonamides, including the challenges associated with the total synthesis, the evolution of our synthetic strategies, structural reassignment, synthesis of all possible stereoisomeric macrocycles, biological assessment, structure-activity relationship (SAR) studies, etc. Within the ambit of this total synthesis, diverse strategies for macrocyclization were rigorously explored, encompassing the Friedel-Crafts acylation, cyclization involving the aniline NH2 moiety, macrolactamization utilizing Gly-NH2, and Heck macrocyclization methodologies. In addition, an array of intriguing chemical transformations were devised, including but not limited to photo-Fries rearrangement, Wacker oxidation, ligand-free Heck macrocyclization, oxidative cleavage of indole, synthesis of contiguous stereocenters via substrate/reagent-controlled protocols, and simultaneous making and breaking of olefinic moieties. The findings of this investigation revealed a structurally simplified lead compound. Remarkably, the lead compound, while possessing structural simplification in comparison to the intricate solomonamide counterparts, demonstrates equipotent in vivo anti-inflammatory efficacy.

Synthesis, biological evaluation and docking studies of silicon incorporated diarylpyrroles as MmpL3 inhibitors: an effective strategy towards development of potent anti-tubercular agents - Vasudevan, N.; Motiwala, Zenia; Ramesh, Remya; Wagh, Sachin B.; Shingare, Rahul D.; Katte, Revansiddha; Anand, Amitesh; Choudhary, Sushil; Kumar, Ajay; Gokhale, Rajesh S.; Kulkarni, Kiran A.; Reddy, D. Srinivasa (European Journal of Medicinal Chemistry, 2023)
Growing global demand for new molecules to treat tuberculosis has created an urgent need to develop novel strategies to combat the menace. BM212 related compounds were found to be potent anti-TB agents and they inhibit mycolic acid transporter, MmpL3, a known potent drug target from Mycobacterium tuberculosis. In order to enhance their inhibitory potency, several silicon analogues of diarylpyrroles related to BM212 were designed, synthesized, and evaluated for anti-tubercular activities. In Alamar blue assay, most of the silicon-incorporated compounds were found to be more potent than the parent compound (BM212), against Mycobacterium tuberculosis (MIC = 1.7 & mu;M, H37Rv). Docking results from the crystal structure of MmpL3 and silicon analogues as pharmacophore model also strongly correlate with the biological assays and suggest that the incorporation of silicon in the inhibitor scaffold could enhance their potency by stabilizing the hydrophobic residues at the binding pocket. The best docking hit, compound 12 showed an MIC of 0.1 & mu;M against H37Rv with an acceptable in vitro ADME profile and excellent selectivity index. Overall, the present study indicates that, the designed silicon analogues, especially compound 12 could be a good inhibitor for an intrinsically flexible drug-binding pocket of MmpL3 and has potential for further development as anti-tubercular agents.
Keywords: antibiotic; BM212; docking studies; MmpL3 inhibitor; Silicon analogue; tuberculosis